Comparison of the therapeutic effects of human umbilical cord blood-derived mesenchymal stem cells and adipose-derived stem cells on erectile dysfunction in a rat model of bilateral cavernous nerve injury - Ti, Yunrong; Yang, Mengbo; Chen, Xinda; Zhang, Ming; Xia, Jingjing; Lv, Xiangguo; Xiao, Dongdong; Wang, Jiucun; Lu, Mujun (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Cavernous nerve injury (CNI) is the leading cause of erectile dysfunction (ED) after radical prostatectomy and pelvic fracture. Transplantation of human adipose-derived stem cells (ASCs) has been widely used to restore erectile function in CNI-ED rats and patients. Umbilical cord blood-derived MSCs (CBMSCs) are similar low immunogenic but more primitive compared to ASCs, and more promising in large-scale commercial applications due to the extensive establishment of cord blood banks. However, whether CBMSCs and ASCs have differential therapeutic efficacy on CNI-ED and the underlying mechanisms are still not clear. Materials and methods: A bilateral cavernous nerve injury (BCNI) rat model was established by crushing the bilateral cavernous nerves, then ASCs and CBMSCs were intra-cavernously injected immediately. Erectile function, masson staining and immunoflourescence analyses of penile tissues were assessed at 4 and 12 weeks. PKH-26 labeled ASCs or CBMSCs were intracavernously injected to determine the presence and differentiation of ASCs or CBMSCs in penis at 3 days. In vitro experiments including intracellular ROS detection, mitochondrial membrane potentials assay, EdU cell proliferation staining, cell apoptosis assay and protein chip assay were conducted to explore the underlying mechanism of CBMSCs treatment compared with ASCs. Results: CBMSCs injection significantly restored erectile function, rescued the loss of cavernous corporal smooth muscles and increased the ratio of smooth muscle to collagen. PKH26 labeled CBMSCs or ASCs did not colocalize with endothelial cells or smooth muscle cells in corpus cavernosum. Besides, the conditioned medium (CM) of CBMSCs could significantly inhibit the oxidative stress, elevate the mitochondria membrane potential and proliferation of schwann cells. The better therapeutic effects were observed in CBMSCs group compared to ASCs group both in vivo and in vitro. In addition, the content of neurotrophic factors and matrix metalloproteinases in CBMSCs-CM, especially NT4, VEGF, MMP1 and MMP3 was significantly higher than that of ASCs-CM. Conclusion: Intracavernous injection of CBMSCs exhibited a better erectile function restoration than ASCs in CNI-ED rats owing to richer secretory factors, which can promote nerve regeneration and reduce extracellular matrix deposition. CBMSCs transplantation would be a promising therapeutic strategy for CNI-ED regeneration in the future.